An Earth‐Abundant Ni‐Based Single‐Atom Catalyst for Selective Photodegradation of Pollutants. Issue 7 (28th May 2021) - Vilé, Gianvito; Sharma, Priti; Nachtegaal, Maarten; Tollini, Flavio; Moscatelli, Davide; Sroka-Bartnicka, Anna; Tomanec, Ondrej; Petr, Martin; Filip, Jan; Pieta, Izabela S.; Zbořil, Radek; Gawande, Manoj B.
Abstract : Highly efficient catalytic technologies are urgently needed to remove pharmaceutical pollutants from water. In this work, the preparation, characterization, and photocatalytic performance of an earth‐abundant Ni‐based heterogeneous catalyst featuring highly dispersed Ni species over nanosheets of carbon nitride are reported. The absence of any metallic nickel phase has been confirmed by spectrometric analyses, unveiling the NiN environment for the metal centers and attaining synergistic interfacial carrier transfer via NNiN coordination. By combining advanced characterizations with kinetic investigations, it is demonstrated that these newly formed isolated single atoms of Ni act as a bridge, facilitating faster electron transfer, increasing the charge density on Ni, and reducing the photocarrier transfer barrier. Compared to literature precedents, this substantially enhances the degradation of gemfibrozil, a model pharmaceutical pollutant found in wastewater, reducing the formation of toxic benzenic byproducts during photooxidation. This effect, which is not observed over conventional nanoparticle‐based materials, discriminates the role of single‐atom and nanoparticle‐based catalysis during degradation of pollutants. This work opens new avenues in designing selective and earth‐abundant photocatalysts for advanced oxidation processes, showing the importance of atom coordination to control the surface and catalytic properties of single‐atom materials. Abstract : Due to synergistic interfacial carrier transfer via NNiN coordination, Ni‐based single‐atom catalysts efficiently and selectively degrade contaminants of emerging concern, including pharmaceuticals in water.